Respuesta :

Answer:

good luck

Step-by-step explanation:

2/c-2 - 3/c+2=7/c^2 - 4

- and + is the same and x with % is the same so

2+2+4

c+c=c^2

2-3 but the 2 dont cont. it

4+3 it will be 7 soo

7/c^2-4

hope this helps u

need more answer just follow me and give me Brainliest ty

Answer:

c = 3

Step-by-step explanation:

Given

[tex]\frac{2}{c-2}[/tex] - [tex]\frac{3}{c+2}[/tex] = [tex]\frac{7}{c^2-4}[/tex] ← factor the difference of squares

[tex]\frac{2}{c-2}[/tex] - [tex]\frac{3}{c+2}[/tex] = [tex]\frac{7}{(c-2)(c+2)}[/tex]

Multiply through by (c - 2)(c + 2) to clear the fractions

2(c + 2) - 3(c - 2) = 7 ← distribute and simplify left side

2c + 4 - 3c + 6 = 7

- c + 10 = 7 ( subtract 10 from both sides )

- c = - 3 ( multiply both sides by - 1 )

c = 3

ACCESS MORE